El cortometraje como recurso didáctico para el desarrollo de la destreza oral en las clases de E/LE: una propuesta didáctica en el 2º año de la enseñanza media en la escuela Sistema de Ensino Vestibulando, Abaetetuba-PA - TORRES, Iris Andrade (2021)
The current society requires a constant changing in the educational scenario. Considering the heterogeneity of the language, which suggests a study not only of its structure but also allows the development of the linguistics competency and the student's critical thinking, this study describes the positive result of a didactic proposal implemented by using audiovisual resources (short-film) to A1 level. The objective of this research is to advance the skills that compose the Spanish language education and learning, especially the orality. This study has confirmed that the usage of shot-film in the E/LE classes, created the expected result to the students; therefore, the short-film has viability to continue being used in the E/LE classes, because it is an excellent educational tool to be used in the beginner’s level since it enhances the communication skills. Whit respect to the methodology implemented, the study was conducted through a literature review and an analysis of a specific case study. As a theoretical reference, for the short-film concept, the ideas of the following authors were assessed, Ribeiro (2013), Alcântara (2014), among others. For the importance of the learning sources to study a foreign language, the concepts of the following authors were reviewed, García-de-Stefani (2010), Napolitano (2003), among others.